Experimental study on dynamic behavior of GFRP-to-concrete interface. (1st July 2016) - Huo, Jingsi; Liu, Jingya; Lu, Yuan; Yang, Jin; Xiao, Yan
Highlights: Impact loading has significant influence on the strain distribution in GFRP sheet. Proposed bond–slip model can reasonably simulate the dynamic bond behavior. Design proposal can predict the effective bond length and ultimate bond strength. Abstract: Glass fiber reinforced polymer (GFRP) sheets/plates are widely used to strengthen deficient reinforced concrete (RC) structures. Existing studies show that the effectiveness of externally bonded FRP materials generally depends on the bond between the FRP element and concrete. Most of the researches developed so far have focused on the bond behavior of FRP sheet-concrete interface under static loading. In this work, the bond behavior was experimentally investigated from the dynamic standpoint, through the drop-mass impact test method, with the aim of highlighting the effect of the loading rate on the bond strength. The test results showed that the strain distribution gradient of GFRP sheets under impact loading was larger than under static loading, and that the loading rate significantly influences the bond strength, while only moderately affecting the effective bond length. A practical bond–slip model is here proposed to simulate the GFRP-to-concrete interface bond behavior under dynamic conditions, which considers the strain-rate effect based on the recommendations given in CEB for the strength of concrete under impact loading. Furthermore, starting from the equations given in some existing guidelines, a design proposal is developed to accurately predict the effective bond length and the bond strength of GFRP-to-concrete interface under impact loading.